The Role of CXCR2, MMP-2, and MMP-9 in the Pathogenesis of Placenta Accreta: A Molecular Expression Study - Putri Mirani; Krisna Murti; Peby Maulina Lestari; Iche Andriyani Liberty; Cindy Kesty; Hana Andrina; Bella Stevanny (Medicina)
Background and Objectives: The pathogenesis of placenta accreta spectrum disorder (PASD) is influenced by the inflammatory process. Therefore, the examination of biomarkers related to the inflammatory process, namely matrix metalloproteinase (MMP) and CXC motif chemokine receptor 2 (CXCR2), is expected to bring researchers to a bright spot regarding the pathogenesis of PASD. This study analyzes the role of CXCR2, MMP-2, and MMP-9 in the pathogenesis of PASD. Materials and Methods: An observational study with a case–control design was conducted to assess differences in the mean density of CXCR2, MMP-2, and MMP-9 immunostaining in placental and uterine tissue in 17 patients with PASD and 34 patients without PASD at the Department of Obstetrics and Gynecology, Dr. Mohammad Hoesin Hospital Palembang. The expression of CXCR2, MMP-2, and MMP-9 was measured by immunohistochemistry analysis. The data were analyzed using STATA version 15. Results: There were no significant differences in the mean levels of MMP-2 expression in patients with and without PASD. There were significant differences in the expression of placental CXCR2 (p = 0.003), uterine CXCR2 (p < 0.001), and uterine MMP-9 (p = 0.018) in patients with and without PASD. Conclusions: CXCR2 and MMP-9 may play a role in the pathogenesis of PASD.